A self-sensing magnetic response phase change driving material and its preparation method and application

By loading soft magnetic nanoparticles and two -dimensional conductive materials in phase -driven materials, and scattered in silicon rubber, the self -sensing function is realized, and the problem of difficulty in real time in real time. Double -functional materials.

CN115558467BActive Publication Date: 2025-01-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211297960.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2025-01-28
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The existing phase change driving materials are difficult to perceive the material state in real time during deformation, and the material complexity is high, which limits its application prospects.

Method used

The soft magnetic nanoparticles are loaded on the two -dimensional conductive material by using the water heat method, and it is evenly scattered in the silicon rubber prefabrication to form a self -sensor magnetic response phase variable drive material. This material generates heat under the transition magnetic field, leading to phase change, and the dielectric constant changes in the two -dimensional conductive materials are used for real -time sensing.

Benefits of technology

The dual functions of driving and self -sensing are realized. It has the characteristics of large change, good stability, fast response speed, and high sensitivity. It is simple to prepare, low cost, and suitable for artificial muscles and flexible actuators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115558467B_ABST
    Figure CN115558467B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-sensing magnetic response phase change driving material and its preparation method and application. The preparation method comprises: using a hydrothermal method to load soft magnetic nanoparticles on a two-dimensional conductive material to obtain a two-dimensional conductive material loaded with soft magnetic nanoparticles; uniformly dispersing the two-dimensional conductive material loaded with soft magnetic nanoparticles and a low boiling point liquid in a silicone rubber prepolymer to form a first mixture; uniformly dispersing the two-dimensional conductive material loaded with soft magnetic nanoparticles and a low boiling point liquid in a silicone rubber prepolymer curing agent to form a second mixture; and subjecting the mixed reaction system containing the first mixture and the second mixture to a curing reaction to obtain a self-sensing magnetic response phase change driving material. The self-sensing magnetic response phase change driving material prepared by the present invention can realize the dual functions of driving and self-sensing, and has the characteristics of large deformation, good stability, fast response speed, high sensitivity, etc., and is simple to prepare, low cost, and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of intelligent phase-change composite materials, and in particular relates to a self-sensing magnetic response phase-change driving material and a preparation method and application thereof. Background Art

[0002] Liquid-gas phase change materials can absorb energy in a thermal environment. When the temperature reaches the boiling point of the material, a phase change occurs, from liquid to gas. The phase change process is accompanied by volume expansion, which can convert thermal energy into expansion driving force. After the heat supply is stopped, the phase change material changes from gas back to liquid, releasing heat, and the volume begins to shrink. Magnetic response phase change drive material is a liquid-gas phase change material that changes phase when the temperature is increased under the action of an alternating magnetic field. Due to its high sensitivity, large deformation and non-contact characteristics, it has broad application prospects in biomedicine, artificial muscles, flexible actuators and other fields.

[0003] The real-time sensing and feedback capabilities during deformation are conducive to the realization of more powerful functions and wider environmental adaptability of materials. The current phase change drive materials have poor conductivity, and it is difficult to sense the real-time state of the material during deformation through changes in resistance. Integrating sensors on the surface of the material will greatly increase the complexity of the material, which seriously limits its further application. Therefore, it is urgent to develop a phase change drive material that integrates deformation drive and sensing characteristics. Summary of the invention

[0004] The main purpose of the present invention is to provide a self-sensing magnetic response phase change driving material and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] An embodiment of the present invention provides a method for preparing a self-sensing magnetic response phase change driving material, which comprises:

[0007] The soft magnetic nanoparticles are loaded on the two-dimensional conductive material by a hydrothermal method to obtain the two-dimensional conductive material loaded with the soft magnetic nanoparticles;

[0008] Uniformly dispersing the two-dimensional conductive material loaded with soft magnetic nanoparticles and the low boiling point liquid in the silicone rubber prepolymer to form a first mixture;

[0009] Uniformly dispersing the two-dimensional conductive material loaded with soft magnetic nanoparticles and the low boiling point liquid in the silicone rubber prepolymer curing agent to form a second mixture;

[0010] And, a mixed reaction system including the first mixture and the second mixture is subjected to a curing reaction at 20 to 80° C. for 1 to 48 hours to obtain a self-sensing magnetic response phase change driving material.

[0011] An embodiment of the present invention also provides a self-sensing magnetically responsive phase-change driving material prepared by the aforementioned preparation method, wherein the self-sensing magnetically responsive phase-change driving material includes a dispersion medium and a dispersed phase, wherein the dispersed phase is uniformly dispersed in the dispersion medium, wherein the dispersion medium includes silicone rubber, and wherein the dispersed phase includes a two-dimensional conductive material loaded with soft magnetic nanoparticles and a low-boiling-point liquid, wherein the soft magnetic nanoparticles in the two-dimensional conductive material loaded with soft magnetic nanoparticles are loaded on the two-dimensional conductive material, and the low-boiling-point liquid is uniformly dispersed in the dispersion medium in the form of droplets.

[0012] The embodiment of the present invention also provides the use of the aforementioned self-sensing magnetic response phase change driving material in the field of flexible actuators or artificial muscles.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] (1) The soft magnetic nanoparticles in the self-sensing magnetic response phase change driving material of the present invention have good magnetothermal conversion performance. The material generates a large amount of heat in the alternating magnetic field, causing the low-boiling point liquid inside the elastomer to vaporize, expand and deform;

[0015] (2) The two-dimensional conductive material in the present invention has a high dielectric constant. Doping it in an elastomer with a low dielectric constant can effectively improve the signal-to-noise ratio of the material's capacitive sensing. During the expansion of the elastomer, the low-boiling-point liquid undergoes a liquid-gas phase transition, the dielectric constant decreases, and the two-dimensional conductive material gradually disperses due to deformation, and its dielectric constant between the electrode plates also decreases. At the same time, the distance between the electrode plates increases. Under the combined effect of these three factors, the capacitance of the self-sensing magnetic response phase change driving material decreases rapidly, thereby achieving real-time perception of its deformation.

[0016] (3) The self-sensing magnetically responsive phase change driving material of the present invention can realize the dual functions of driving and self-sensing, and has the characteristics of large deformation, good stability, fast response speed, high sensitivity, etc., and is simple to prepare, low cost, and can be recycled. It has broad application prospects in the fields of artificial muscles, flexible actuators, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 is a diagram showing the deformation and sensing of a self-sensing magnetically responsive phase-change actuated material in a typical embodiment of the present invention;

[0019] Figure 2 is a flow chart of the preparation of a self-sensing magnetically responsive phase-change driving material in a typical embodiment of the present invention;

[0020] Figure 3 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Example 1 of the present invention and the temperature in an alternating magnetic field;

[0021] Figure 4 is a curve diagram showing the relationship between the capacitance and the compression ratio of the magnetic response device prepared in Example 1 of the present invention in an alternating magnetic field;

[0022] Figure 5 is a curve diagram showing the relationship between the dielectric constant of the magnetic response device prepared in Example 1 of the present invention and the frequency;

[0023] Figure 6 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Example 2 of the present invention and the temperature in an alternating magnetic field;

[0024] Figure 7 is a curve diagram showing the relationship between the capacitance and the compression ratio of the magnetic response device prepared in Example 2 of the present invention in an alternating magnetic field;

[0025] Figure 8 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Example 3 of the present invention and the temperature in an alternating magnetic field;

[0026] Fig. 9 is a curve diagram showing the relationship between capacitance and compression ratio of the magnetic response device prepared in Example 3 of the present invention in an alternating magnetic field;

[0027] Fig.10 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Example 4 of the present invention and the temperature in an alternating magnetic field;

[0028] Fig.11 is a curve diagram showing the relationship between capacitance and compression ratio of the magnetic response device prepared in Example 4 of the present invention in an alternating magnetic field;

[0029] Fig.12 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Example 5 of the present invention and the temperature in an alternating magnetic field;

[0030] Fig.13 is a curve diagram showing the relationship between capacitance and compression ratio of the magnetic response device prepared in Example 5 of the present invention in an alternating magnetic field;

[0031] Figure 14a-14b is a photograph of the fishbone structure actuator prepared in Example 6 of the present invention being transformed from a two-dimensional planar structure to a three-dimensional structure;

[0032] Fig.15is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Comparative Example 1 of the present invention and the temperature in an alternating magnetic field;

[0033] Fig.16 is a curve diagram showing the relationship between the capacitance and the compression ratio of the magnetic response device prepared in Comparative Example 1 of the present invention in an alternating magnetic field;

[0034] Fig.17 is a curve diagram showing the relationship between the expansion force of the magnetic response device prepared in Comparative Example 2 of the present invention and the temperature in an alternating magnetic field;

[0035] Fig.18 is a curve diagram showing the relationship between the capacitance and the compression ratio of the magnetic response device prepared in Comparative Example 2 of the present invention in an alternating magnetic field;

[0036] Fig.19 is a curve diagram showing the relationship between the dielectric constant of the composite material prepared in Comparative Example 3 of the present invention and the frequency;

[0037] Fig. 20 It is the change of capacitance during the deformation of the artificial muscle prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0038] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. It mainly provides a liquid-gas phase change material with both driving and sensing functions and its preparation method and application, so as to overcome the shortcomings of the existing liquid-gas phase change material that only has a driving function and cannot timely feedback the changes in the driving process.

[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a self-sensing magnetic response phase change driving material includes:

[0041] The soft magnetic nanoparticles are loaded onto the two-dimensional conductive material by a hydrothermal method to obtain a two-dimensional conductive material loaded with soft magnetic nanoparticles (also referred to as a two-dimensional conductive material / soft magnetic nanoparticle composite material);

[0042] The two-dimensional conductive material loaded with soft magnetic nanoparticles and the low boiling point liquid are uniformly dispersed in a silicone rubber prepolymer (also referred to as silicone rubber A agent) to form a first mixture;

[0043] The two-dimensional conductive material loaded with soft magnetic nanoparticles and the low boiling point liquid are uniformly dispersed in a silicone rubber prepolymer curing agent (also referred to as silicone rubber B agent) to form a second mixture;

[0044] And, a mixed reaction system including the first mixture and the second mixture is subjected to a curing reaction at 20 to 80° C. for 1 to 48 hours to obtain a self-sensing magnetic response phase change driving material.

[0045] In some preferred embodiments, the two-dimensional conductive material includes MXene and / or graphene, but is not limited thereto.

[0046] In some preferred embodiments, the soft magnetic nanoparticles include any one of ferroferric oxide, permalloy, and sendust, or a combination of two or more thereof, and are not limited thereto.

[0047] In some preferred embodiments, the low boiling point liquid includes any one of methanol, ethanol, Novec 7000, trichlorotrifluoroethane or a combination of two or more thereof, but is not limited thereto.

[0048] Furthermore, the boiling point of the low-boiling-point liquid is less than 90°C.

[0049] In some preferred embodiments, the silicone rubber prepolymer includes any one or a combination of two or more of Ecoflex 00-50 prepolymer, Ecoflex00-30 prepolymer, Dragon skin 30 prepolymer, Beshow Skin30 prepolymer, Sylgard 184 prepolymer, and T10 prepolymer, and is not limited thereto.

[0050] In some preferred embodiments, the silicone rubber prepolymer curing agent includes any one or a combination of two or more of Ecoflex 00-50 prepolymer curing agent, Ecoflex 00-30 prepolymer curing agent, Dragon skin 30 prepolymer curing agent, Beshow Skin30 prepolymer curing agent, Sylgard 184 prepolymer curing agent, and T10 prepolymer curing agent, and is not limited thereto.

[0051] In some preferred embodiments, the side chain groups of the silicone rubber prepolymer and the silicone rubber prepolymer curing agent can react with each other to form a silicone rubber having a three-dimensional network macromolecular structure.

[0052] Furthermore, the silicone rubber prepolymer and silicone rubber prepolymer curing agent should have the characteristics of low modulus, stretchability, easy doping and low cost.

[0053] In some preferred embodiments, the mass ratio of the two-dimensional conductive material to the soft magnetic nanoparticles is 1 to 30:100.

[0054] Furthermore, the mass ratio of the two-dimensional conductive material to the soft magnetic nanoparticles is 2 to 20:100;

[0055] In some preferred embodiments, the mass ratio of the two-dimensional conductive material loaded with soft magnetic nanoparticles, the low boiling point liquid and the silicone rubber prepolymer in the first mixture is 30-80:5-40:100;

[0056] In some preferred embodiments, the mass ratio of the two-dimensional conductive material loaded with soft magnetic nanoparticles, the low boiling point liquid and the silicone rubber prepolymer curing agent in the second mixture is 30-80:5-40:100.

[0057] Another aspect of an embodiment of the present invention further provides a self-sensing magnetically responsive phase change driving material obtained by the aforementioned preparation method, wherein the self-sensing magnetically responsive phase change driving material includes a dispersion medium and a dispersed phase, wherein the dispersed phase is uniformly dispersed in the dispersion medium, wherein the dispersion medium includes silicone rubber, and wherein the dispersed phase includes a two-dimensional conductive material loaded with soft magnetic nanoparticles and a low-boiling-point liquid, wherein the soft magnetic nanoparticles in the two-dimensional conductive material loaded with soft magnetic nanoparticles are loaded on the two-dimensional conductive material, and the low-boiling-point liquid is uniformly dispersed in the dispersion medium in the form of droplets.

[0058] In some preferred embodiments, the mass ratio of the two-dimensional conductive material loaded with soft magnetic nanoparticles to the dispersion medium in the self-sensing magnetic-responsive phase change driving material is 30 to 80:100.

[0059] Furthermore, the mass ratio of the two-dimensional conductive material loaded with soft magnetic nanoparticles to the dispersion medium in the self-sensing magnetic response phase change driving material is 40 to 70:100.

[0060] In some preferred embodiments, the mass ratio of the low boiling point liquid to the dispersion medium in the self-sensing magnetic response phase change driving material is 5 to 40:100.

[0061] Furthermore, the mass ratio of the low boiling point liquid to the dispersion medium in the self-sensing magnetic response phase change driving material is 10 to 30:100.

[0062] In some preferred embodiments, the silicone rubber includes any one or a combination of two or more of Ecoflex 00-50, Ecoflex 00-30, Dragonskin 30, Beshow Skin30, Sylgard 184, T10, etc., and is not limited thereto.

[0063] The soft magnetic particles in the self-sensing magnetic response phase change driving material of the present invention serve as a heat source, and have a high magnetothermal conversion rate. Under the action of the alternating magnetic field, a large amount of heat is generated, causing the low-boiling point liquid inside the elastomer to vaporize and expand, thereby causing the elastomer to deform greatly. After the magnetic field is turned off, the soft magnetic particles stop supplying heat, the temperature drops, and the low-boiling point liquid liquefies and shrinks again. At this time, the elastomer returns to its original shape.

[0064] The two-dimensional conductive material in the self-sensing magnetic response phase change driving material of the present invention increases the conductivity of the elastomer. During the deformation process of the elastomer, the density of the conductive material per unit volume and the transition of the gas-liquid phase of the low-boiling liquid will change the dielectric constant of the material, thereby changing the capacitance of the elastomer. Due to the capacitive sensing principle, the elastomer has self-sensing ability. The deformation and sensing demonstration diagram of the self-sensing magnetic response phase change driving material is shown in the figure below. Figure 1 shown.

[0065] The self-sensing magnetically responsive phase-change driving material of the present invention realizes the dual-functional synergy of driving and self-sensing, and has the characteristics of large deformation, fast response speed, high sensitivity, low cost, etc.

[0066] Another aspect of the embodiments of the present invention further provides the use of the aforementioned self-sensing magnetic response phase change driving material in the field of flexible actuators or artificial muscles.

[0067] In summary, the self-sensing magnetically responsive phase change driving material of the present invention can realize the dual functions of driving and self-sensing, and has the characteristics of large deformation, good stability, fast response speed, high sensitivity, etc. It is simple to prepare, low cost, and can be recycled. It has broad application prospects in the fields of artificial muscles, flexible actuators, etc.

[0068] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0069] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0070] Example 1

[0071] (1) Weigh 1.5 g of ferroferric oxide and 0.1 g of MXene, and prepare MXene / Fe3O4 composite material by hydrothermal method.

[0072] (2) Weigh 0.15 g of MXene / Fe3O4 composite material and 2.0 g of methanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber agent A, and stir them thoroughly for 5 min to obtain a premixed agent A;

[0073] (3) Weigh 0.15 g of MXene / Fe3O4 composite material and 2.0 g of methanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber B agent, and stir them thoroughly for 5 min to obtain a premixed B agent;

[0074] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0075] (5) Add the composite slurry into a mold, seal the mold, and cure it at 23° C. for 5 h to obtain a self-sensing magnetic response phase change driving material. Figure 2 This is the preparation flow chart of self-sensing magnetic response phase change driving materials. Figure 3 and Figure 4 The following are the relationship curves of expansion force with temperature and capacitance with compression ratio when the magnetic response device is placed in an alternating magnetic field with a frequency of 30kHz. Figure 5 It is a curve diagram of the relationship between the dielectric constant of the magnetic response device and the frequency.

[0076] Example 2

[0077] (1) Weigh 2.0 g of ferroferric oxide and 0.2 g of graphene, and prepare a graphene / Fe3O4 composite material by a hydrothermal method.

[0078] (2) Weigh 0.3 g of graphene / Fe3O4 composite material and 3.5 g of ethanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber agent A, and stir them thoroughly for 5 min to obtain a premixed agent A;

[0079] (3) Weigh 0.3 g of graphene / Fe3O4 composite material and 3.5 g of ethanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber B agent, and stir them thoroughly for 5 min to obtain a premixed B agent;

[0080] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0081] (5) Add the composite slurry into a mold, seal the mold, and cure it at 23° C. for 5 h to obtain a self-sensing magnetic response phase change driving material. Figure 6 and Figure 7 They are respectively a curve diagram of the relationship between expansion force and temperature and a curve diagram of the relationship between capacitance and compression ratio when the magnetic response device is placed in an alternating magnetic field with a frequency of 30kHz.

[0082] Example 3

[0083] (1) Weigh 1.0 g of beryllium molybdenum alloy and 0.1 g of graphene, and prepare a graphene / beryllium molybdenum alloy composite material by a hydrothermal method.

[0084] (2) Weigh 0.2 g of graphene / beryllium molybdenum alloy composite material and 2.0 g of Novec 7000 solution, add them into 10 g of Ecoflex 00-50 silicone rubber agent A, and stir them thoroughly for 5 minutes to obtain a premixed agent A;

[0085] (3) Weigh 0.2 g of graphene / beryllium molybdenum alloy composite material and 2.0 g of Novec 7000 solution, add them into 10 g of Ecoflex 00-50 silicone rubber B agent, and stir them thoroughly for 5 minutes to obtain a premixed B agent;

[0086] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0087] (5) Add the composite slurry into a mold, seal the mold, and cure it at 23° C. for 4 hours to obtain a self-sensing magnetic response phase change driving material. Figure 8 and Fig. 9 They are respectively a curve diagram of the relationship between expansion force and temperature and a curve diagram of the relationship between capacitance and compression ratio when the magnetic response device is placed in an alternating magnetic field with a frequency of 30kHz.

[0088] Example 4

[0089] (1) Weigh 1.5 g of sendust and 0.1 g of MXene, and prepare a MXene / sendust composite material by a hydrothermal method.

[0090] (2) Weigh 0.25 g of MXene / FeSiAl composite material and 4.0 g of trichlorotrifluoroethane solution, add them into 10 g of Ecoflex 00-50 silicone rubber agent A, and stir them thoroughly for 5 min to obtain a premixed agent A;

[0091] (3) Weigh 0.25 g of MXene / FeSiAl composite material and 4.0 g of trichlorotrifluoroethane solution, add them into 10 g of Ecoflex 00-50 silicone rubber B agent, and stir them thoroughly for 5 min to obtain a premixed B agent;

[0092] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0093] (5) Add the composite slurry into a mold, seal the mold, and cure it at 23° C. for 4 hours to obtain a self-sensing magnetic response phase change driving material. Fig.10 and Fig.11They are respectively a curve diagram of the relationship between expansion force and temperature and a curve diagram of the relationship between capacitance and compression ratio when the magnetic response device is placed in an alternating magnetic field with a frequency of 30kHz.

[0094] Example 5

[0095] (1) Weigh 1.0 g of ferroferric oxide and 0.1 g of MXene, and prepare MXene / Fe3O4 composite material by hydrothermal method.

[0096] (2) Weigh 0.1 g of MXene / Fe3O4 composite material and 2.0 g of ethanol solution, add them into 10 g of Dragon skin 30 silicone rubber agent A, and stir them thoroughly for 5 min to obtain premixed agent A;

[0097] (3) Weigh 0.1 g of MXene / Fe3O4 composite material and 2.0 g of ethanol solution, add them into 10 g of Dragon skin 30 silicone rubber B agent, and stir them thoroughly for 5 min to obtain a premixed B agent;

[0098] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0099] (5) The composite slurry is added into a mold, the mold is sealed, and cured at 60° C. for 4 h to obtain a self-sensing magnetic response phase change driving material. Fig.12 and Fig.13 They are respectively a curve diagram of the relationship between expansion force and temperature and a curve diagram of the relationship between capacitance and compression ratio when the magnetic response device is placed in an alternating magnetic field with a frequency of 30kHz.

[0100] Example 6

[0101] (1) Weigh 1.5 g of ferroferric oxide and 0.1 g of MXene, and prepare MXene / Fe3O4 composite material by hydrothermal method.

[0102] (2) Weigh 0.15 g of MXene / Fe3O4 composite material and 2.0 g of methanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber agent A, and stir them thoroughly for 5 min to obtain a premixed agent A;

[0103] (3) Weigh 0.15 g of MXene / Fe3O4 composite material and 2.0 g of methanol solution, add them into 10 g of Ecoflex 00-30 silicone rubber B agent, and stir them thoroughly for 5 min to obtain a premixed B agent;

[0104] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0105] (5) Take 8g of the composite slurry and put it into a 10cc barrel. Select a printing pressure of 0.2MPa and a moving speed of 20mm / s. Directly print on carbon paper to obtain a magnetically responsive fishbone structure actuator. Figure 14- Fig.14b This is a photo of the fishbone structure actuator transforming from a two-dimensional planar structure to a three-dimensional structure.

[0106] Comparative Example 1

[0107] (1) Weigh 1.5 g of ferroferric oxide and 0.1 g of MXene, and prepare MXene / Fe3O4 composite material by hydrothermal method.

[0108] (2) Weigh 0.1 g of MXene / Fe3O4 composite material and 2.0 g of ethanol solution, add them into 10 g of PDMS1700A agent, and stir them thoroughly for 5 min to obtain a premixed A agent;

[0109] (3) Weigh 0.1 g of MXene / Fe3O4 composite material and 2.0 g of ethanol solution, add them into 10 g of PDMS1700B agent, and stir them thoroughly for 5 min to obtain premixed B agent;

[0110] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0111] (5) The composite slurry is added into a mold, the mold is sealed, and cured at 23° C. for 5 h to obtain a composite material. Fig.15 and Fig.16 The graphs are respectively the relationship between expansion force and temperature and the relationship between capacitance and compression ratio when the composite material is placed in an alternating magnetic field with a frequency of 30kHz. It can be seen that the expansion force and capacitance changes of the composite material are obviously not as good as the self-sensing magnetic response phase change driving material prepared in Examples 1-5.

[0112] Comparative Example 2

[0113] (1) Weigh 1.0 g of beryllium molybdenum alloy and 0.1 g of graphene, and prepare a graphene / beryllium molybdenum alloy composite material by a hydrothermal method.

[0114] (2) Weigh 0.15 g of graphene / beryllium molybdenum alloy composite material and 2.5 g of edible oil solution, add them into 10 g of Ecoflex00-50 silicone rubber agent A, and stir them thoroughly for 5 minutes to obtain a premixed agent A;

[0115] (3) Weigh 0.15 g of graphene / beryllium molybdenum alloy composite material and 2.5 g of edible oil solution, add them into 10 g of Ecoflex00-50 silicone rubber B agent, and stir them thoroughly for 5 minutes to obtain a premixed B agent;

[0116] (4) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0117] (5) The composite slurry is added into a mold, the mold is sealed, and cured at 23° C. for 4 h to obtain a composite material. Fig.17 and Fig.18 The graphs are respectively the relationship between expansion force and temperature and the relationship between capacitance and compression ratio when the composite material is placed in an alternating magnetic field with a frequency of 30kHz. It can be seen that the expansion force and capacitance changes of the composite material are obviously not as good as the self-sensing magnetic response phase change driving material prepared in Examples 1-5.

[0118] Comparative Example 3

[0119] (1) Weigh 0.1 g of ferrosoferric oxide, add it to 10 g of Ecoflex 00-30 silicone rubber agent A, and stir thoroughly for 5 minutes to obtain a premixed agent A;

[0120] (2) Weigh 0.1 g of ferrosoferric oxide, add it to 10 g of Ecoflex 00-30 silicone rubber agent B, and stir thoroughly for 5 minutes to obtain a premixed agent B;

[0121] (3) Add premixed agent A and premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry.

[0122] (4) The composite slurry is added into a mold, the mold is sealed, and cured at 23° C. for 5 h to obtain a composite material. Fig.19 : is a curve diagram of the relationship between the dielectric constant of the composite material and the frequency. It can be seen that the dielectric constant of the composite material is significantly lower than that of the self-sensing magnetic response phase change driving material prepared in Example 1.

[0123] Example 7

[0124] The method of this embodiment is the same as that of embodiment 1, and a self-sensing magnetic response phase change driver is prepared by direct writing 3D printing technology, that is, an artificial muscle with integrated drive sensing. The thigh and calf are connected by an elastomer, and the elastomer will stretch the calf during expansion, and conversely, the elastomer will retract the calf during contraction. During the driving process, the change in capacitance when the muscle is stretched and contracted is tested, and the bending angle of the leg can be known through the feedback capacitance value, and precise control can be applied according to the required angle. Fig. 20 The change of capacitance during the deformation of the artificial muscle.

[0125] To sum up, through the above technical scheme, the self-sensing magnetic response phase change driving material provided by the present invention realizes the dual functional synergy of driving and self-sensing, and has the characteristics of large deformation, good stability, fast response speed, high sensitivity, etc., and is simple to prepare and low in cost.

[0126] In addition, the inventors also referred to the preparation methods of Examples 1-7 and conducted experiments with other raw materials and conditions listed in the present invention, and also successfully produced self-sensing magnetic response phase change driving materials with large deformation, good stability, fast response speed and low cost.

[0127] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. Use of self-sensing magnetic response phase change driving material in the field of flexible actuators or artificial muscles, characterized in that: The self-sensing magnetic response phase change driving material is capacitive sensing, and the preparation method of the self-sensing magnetic response phase change driving material includes: (1) Weigh 1.0 g of beryllium molybdenum alloy and 0.1 g of graphene, and prepare a graphene / beryllium molybdenum alloy composite material by a hydrothermal method; (2) Weigh 0.2 g of graphene / beryllium molybdenum alloy composite material and 2.0 g of Novec 7000 solution, add them into 10 g of Ecoflex 00-50 silicone rubber agent A, and stir them thoroughly for 5 minutes to obtain a premixed agent A; the Ecoflex 00-50 silicone rubber agent A is Ecoflex 00-50 prepolymer; (3) Weigh 0.2 g of graphene / beryllium molybdenum alloy composite material and 2.0 g of Novec 7000 solution, add them into 10 g of Ecoflex 00-50 silicone rubber agent B, and stir them thoroughly for 5 minutes to obtain a premixed agent B; the Ecoflex 00-50 silicone rubber agent B is the Ecoflex 00-50 prepolymer curing agent (4) Add the premixed agent A and the premixed agent B into a beaker at a mass ratio of 1:1 and stir for 5 minutes to obtain a composite slurry; (5) Adding the composite slurry into a mold, sealing the mold, and curing it at 23° C. for 4 hours to obtain a self-sensing magnetic response phase change driving material.

Citation Information

Patent Citations

  • Ferroferric oxide / graphene three-dimensional composite structure as well as preparation method and application thereof

    CN104810509A

  • Preparation method of composite phase change material driven by light energy and magnetic energy

    CN113462366A

  • Deformable-variable stiffness dual-function magnetic intelligent material as well as preparation method and application thereof

    CN113583448A